The Flexible Environment and Professional Educators toward the Use of Video in Flipped Learning - I Gusti Agung Yoga Andika; I Putu Ngurah Wage Myartwan; Dewa Ayu Eka Agustini (Linguistics Initiative, 2021)
Globalization and the growth of technology required the students and teachers to improve the learning process. The English instruction was also in-line with the implementation of the technology, such as conducting the flipped learning.  In flipped learning, the teacher enables the student to learn through the online video. Therefore, this research aims to investigate the role of video in flipped learning-based English instruction. The current study was done at SMA Negeri Bali Mandara that involved three participants. The data collection was done through observation, in-depth interviews by using an interview guide, voice record, and online video. The qualitative data was analyzed through the phase of data reduction, data display, and conclusion drawing. The results showed that the students had positive responses and perceptions due to video in the learning process, which enabled them to improve their English skills.